Reading the rabbis : Christian Hebraism in the works of Herbert of Bosham - Visscher, Eva De. (Boston : Brill, 2014)
In Reading the Rabbis Eva De Visscher examines the level of Hebrew scholarship, programme of literal exegesis, and use of Jewish and Christian Hebraist sources in two commentaries on the Psalms by English polymath Herbert of Bosham (c.1120-c.1194).
Machine generated contents note: 1. Herbert of Bosham's Life and Works -- 2. Christian Hebraisms -- 3. Hebraist Commentaries: The Magna Glosatura and the Psalterium Cum Commento -- I. How Much Hebrew did Herbert Know? -- 1. Transliteration of Hebrew Words -- 2. Knowledge of Hebrew Grammar -- 3. Lexical Changes: The Problems of Literal Translation -- II. Hebrew Learning Tools -- 1. Jerome -- 2. Hebrew-Latin Psalters and the Eadwine Psalter -- 3. Hebraico-French Glosses -- Le'azim -- 4. Hebrew-Hebraico-French Glossaries and Proto-dictionaries -- III. Use of Rabbinic Sources -- 1. Magister and Litterator -- 2. Rashi -- 3. Midrash Tehillim -- 4. Talmud/Gamaliel -- 5. Targums -- 6. Menahem ben Saruq and Dunash ibn Labrat -- 7. Oral Sources -- IV. Negotiating Christian and Jewish Authorities -- 1. Paul's Neutralising Influence -- 2. Paul as Christianising Force -- 3. Paul versus the Litteratores -- 4. Herbert on the Fence? -- V. Practice of Literal Exegesis -- 1. Hebraist, Exegete and Polemicist -- 2. Littera and Peshat -- 3. Caro and Spiritus.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Herbert, -- of Bosham, -- active 12th century -- Knowledge -- Judaism; Herbert, -- of Bosham, -- active 12th century; Christian Hebraists -- England -- History -- 12th century; Christianity and other religions -- Relations -- Judaism -- History -- 12th century; Judaism -- Relations -- Christianity -- History -- 12th century; Hébraïsants chrétiens -- Angleterre -- Histoire -- 12e siècle.; Judaïsme -- Relations -- Christianisme -- Histoire -- 12e siècle.; RELIGION -- Judaism -- General; Christian Hebraists; Christianity; Interfaith relations; Judaism; England; 1100-1199; History